Using specialist screening practitioners (SSPs) to increase uptake of bowel scope (flexible sigmoidoscopy) screening: results of a feasibility single-stage phase II randomised trial. Issue 2 (15th February 2019) - McGregor, Lesley M; Skrobanski, Hanna; Ritchie, Mary; Berkman, Lindy; Miller, Hayley; Freeman, Madeleine; Patel, Nishma; Morris, Stephen; Rees, Colin; von Wagner, Christian
Abstract : Objective: To determine the feasibility of specialist screening practitioners (SSPs) offering patient navigation (PN) to facilitate uptake of bowel scope screening (BSS) among patients who do not confirm or attend their appointment. Design: A single-stage phase II trial. Setting: South Tyneside District Hospital, Tyne and Wear, England, UK. Participants: Individuals invited for BSS at South Tyneside District Hospital during the 6-month recruitment period were invited to participate in the study. Intervention: Consenting individuals were randomly assigned to either the PN intervention or usual care group in a 4:1 ratio. The intervention involved BSS non-attenders receiving a phone call from an SSP to elicit their reasons for non-attendance and offer educational, practical and emotional support as required. If requested by the patient, another BSS appointment was then scheduled. Primary outcome measure: The number of non-attenders in the intervention group who were navigated and then rebooked and attended their new BSS appointment. Secondary outcome measures: Barriers to BSS attendance, patient-reported outcomes including informed choice and satisfaction with BSS and the PN intervention, reasons for study non-participation, SSPs' evaluation of the PN process and a cost analysis. Results: Of those invited to take part (n=1050), 152 (14.5%) were randomised into the study: PN intervention=109; usual care=43. Most participants attended their BSS appointment (PN: 79.8%; control: 79.1%) leaving 22 eligible for PN: only two were successfully contacted. SSPs were confident in delivering PN, but were concerned that low BSS awareness and information overload may have deterred patients from taking part in the study. Difficulty contacting patients was reported as a burden to their workload. Conclusions: PN, as implemented, was not a feasible intervention to increase BSS uptake in South Tyneside. Interventions to increase BSS awareness may be better suited to this population. Trial registration number: ISRCTN13314752; Results.